DIVERSIFIKASI KONSUMSI PANGAN POKOK BERBASIS POTENSI LOKAL DALAM MEWUJUDKAN KETAHANAN PANGAN RUMAHTANGGA PEDESAAN DI KECAMATAN SEMIN KABUPATEN GUNUNG KIDUL - Ni Made Suyastiri Y.P (Economic Journal of Emerging Markets, 2008)
The purpose of the research is to inspect and analyze factors which influence consumption diversification system based on local potential to create village housing food tenacity. This research uses descriptive method with survey implementation method. Research area determination uses purposive method and housing sample is taken by proportional stratified random sampling with 50 housing sample.        The result of this research indicate that staple food based on local potential is still dominated by rice followed by cassava and corn. Staple food diversification system is rice, and substitution rice like corn which follows rice-corn, rice-cassava, and rice-corn-cassava pattern in consumption. Factors which influence housing consumption diversification system is food’s price, household income, and number of family memberKeywords: diversification, consumption, staple food